A Variant of the Kleine-Levin Syndrome following Head Trauma - V. S. Kostic; E. Stefanova; M. Svetel; D. Kozic (Behavioural Neurology)
A 19-year-old man developed the Kleine-Levin syndrome three weeks after the head trauma and subsequent neurosurgical evacuation of right-sided, fronto-temporal epidural hematoma. The expression of periodic episodes was observed for hypersomnolence and, to a lesser degree, for behavioral disturbances, while the hyperphagia was constantly present during a period of 1.5 years. These clinical features were associated with the focal, right-sided hypothalamic lesion and ipsilateral posttraumatic parenchymal temporal lobe damage on NMR imaging.